Предмет: Математика,
автор: sergeysizikov32
a) 4а - 6а - 3а + 7 + а - 4= б) -8(x - 3) +4 (x-2) = упростить
Ответы
Автор ответа:
4
а) 4а-6а-3а+7+а-4=-4а+7-4=-4а+3
б) -8(х-3)+4(х-2)=-4(2(х-3)-(х-2))=-4(2х-6-х+2)=-4(х-4)
б) -8(х-3)+4(х-2)=-4(2(х-3)-(х-2))=-4(2х-6-х+2)=-4(х-4)
Watson111:
ошибка в конце
Автор ответа:
1
Всё во вложении на картинке :)
__________________________
С уважением, ╭S╮╭e╮╭c╮╭u╮╭r╮╭e╮
__________________________
С уважением, ╭S╮╭e╮╭c╮╭u╮╭r╮╭e╮
Приложения:
Похожие вопросы
Предмет: Экономика,
автор: epevtsev
Предмет: История,
автор: Аноним
Предмет: Математика,
автор: egorbro00
Предмет: Математика,
автор: Елизавета678
Предмет: Математика,
автор: v89887684827t20